2022
DOI: 10.1021/acs.nanolett.1c05018
|View full text |Cite
|
Sign up to set email alerts
|

In Situ TEM Technique Revealing the Deactivation Mechanism of Bimetallic Pd–Ag Nanoparticles in Hydrogen Sensors

Abstract: Bimetallic Pd–Ag alloy nanoparticles exhibit satisfactory H2-sensing improvements and show application potential for H2 sensor construction. However, the long-term stability of the H2 sensor with Pd–Ag nanoparticles as the catalyst is found to dramatically decrease during operation. Herein, gas-cell in situ transmission electron microscopy (TEM) is used to investigate the failure mechanisms of Pd–Ag nanoparticles under operation conditions. Based on the in situ TEM results, the Pd–Ag nanoparticles have two fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Bimetallic Alloys: Among various noble metal-based bimetallic catalysts (PdAu, PtAu, PdPt, PdCu, AuCu, PtCo, etc.) studied for a variety of catalytic reactions, [199] PtCo is perhaps the most studied catalyst system due to its synergistic catalytic properties for many reactions, especially for fuel cell ORR, which will be discussed in a later section. In an earlier in situ HAADF-STEM study of Pt 3 Co NP after oxygen annealing at 720 °C, [145] a counter-intuitive oxygen-driven process for the core-shell formation is revealed at elevated temperature under oxygen at atmospheric pressure.…”
Section: Multimetallic Catalystsmentioning
confidence: 99%
“…Bimetallic Alloys: Among various noble metal-based bimetallic catalysts (PdAu, PtAu, PdPt, PdCu, AuCu, PtCo, etc.) studied for a variety of catalytic reactions, [199] PtCo is perhaps the most studied catalyst system due to its synergistic catalytic properties for many reactions, especially for fuel cell ORR, which will be discussed in a later section. In an earlier in situ HAADF-STEM study of Pt 3 Co NP after oxygen annealing at 720 °C, [145] a counter-intuitive oxygen-driven process for the core-shell formation is revealed at elevated temperature under oxygen at atmospheric pressure.…”
Section: Multimetallic Catalystsmentioning
confidence: 99%
“…Because of the high surface energy of noble metal NPs, they tend to aggregate quickly at higher operating temperatures, limiting their long-term stability. Wang et al investigated the long-term stability of the H 2 sensor of the bimetallic Pd–Ag alloy nanocatalyst on the ZnO surface by gas-cell in situ transmission electron microscopy (TEM) at higher operating temperature (300 and 500 °C) . They found that at higher operating temperatures, Pd–Ag alloy NPs get coalesced and segregated, resulting in a decline in their catalytic activities and sensing performance.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al investigated the long-term stability of the H 2 sensor of the bimetallic Pd−Ag alloy nanocatalyst on the ZnO surface by gas-cell in situ transmission electron microscopy (TEM) at higher operating temperature (300 and 500 °C). 24 They found that at higher operating temperatures, Pd−Ag alloy NPs get coalesced and segregated, resulting in a decline in their catalytic activities and sensing performance. Therefore, to solve this issue, a core− shell architecture was found to be an effective way to protect the metallic core from being aggregated by a suitable MOS shell.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lu et al reported another Ti-based composite oxide sensing electrode, which has a detection limit of 500 ppb for acetylene [ 29 ]. For on-site detection of trace gases, such as acetylene, miniature gas sensors with high sensing performance and low power consumption have attracted much attention [ 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%